Characteristics of board of directors and financial distress: a Malaysian case - Takiah Mohd Iskandar,; Zulridah Mohd Noor,; Noraini Omar, (Penerbit Universiti Kebangsaan Malaysia, 2012)
This paper examines the relationship between the characteristics of boards of directors and the financial distress of companies listed on Bursa Malaysia. The sample consists of 68 companies whose listing status on Bursa Malaysia was being suspended between 2005 and 2009, under the provision of Practice Note 17 (PN17) of the Bursa Malaysia Listing Requirements. The study develops a multinomial logit regression model to test three categories of PNJ7 listing statuses: re-listed on Bursa Malaysia, remain as PN I 7, and de-listed from Bursa Malaysia. The model relates the listing status to five characteristics ofthe boards of directors as independent variables, specifically leadership structure, equity ownership, board involvement, financial literacy and multiple directorships of board members; and four control variables, namely firm size, leverage, return on assets and audit quality. The study expects that the success of PN1 7 listing outcomes depends on the ability of the board of directors to establish and implement the restructuring plan. The results show that the re-listing of PN17companies is negatively related to financial literacy and equity ownership of the board of directors and positively related to the involvement of the board. The results imply that boards of directors with a lower ownership and financial literacy, but more actively involved, are more capable of overcoming financial difficulties.